Overhydration is a strong predictor of mortality in peritoneal dialysis patients: independently of cardiac failure - Jotterand Drepper, Valérie; Kihm, Lars Philipp; Kälble, Florian; Diekmann, Christian; Seckinger, Jörg; Sommerer, Claudia; Zeier, Martin; Schwenger, Vedat (PLOS ONE, 2016)
Background Overhydration is a common problem in peritoneal dialysis patients and has been shown to be associated with mortality. However, it still remains unclear whether overhydration per se is predictive of mortality or whether it is mainly a reflection of underlying comorbidities. The purpose of our study was to assess overhydration in peritoneal dialysis patients using bioimpedance spectroscopy and to investigate whether overhydration is an independent predictor of mortality. Methods We analyzed and followed 54 peritoneal dialysis patients between June 2008 and December 2014. All patients underwent bioimpedance spectroscopy measurement once and were allocated to normohydrated and overhydrated groups. Overhydration was defined as an absolute overhydration/extracellular volume ratio > 15%. Simultaneously, clinical, echocardiographic and laboratory data were assessed. Heart failure was defined either on echocardiography, as a reduced left ventricular ejection fraction, or clinically according to the New York Heart Association functional classification. Patient survival was documented up until December 31st 2014. Factors associated with mortality were identified and a multivariable Cox regression model was used to identify independent predictors of mortality. Results Apart from higher daily peritoneal ultrafiltration rate and cumulative diuretic dose in overhydrated patients, there were no significant differences between the 2 groups, in particular with respect to gender, body mass index, comorbidity and cardiac medication. Mortality was higher in overhydrated than in euvolemic patients. In the univariate analysis, increased age, overhydration, low diastolic blood pressure, raised troponin and NTproBNP, hypoalbuminemia, heart failure but not CRP were predictive of mortality. After adjustment, only overhydration, increased age and low diastolic blood pressure remained statistically significant in the multivariate analysis. Conclusions Overhydration remains an independent predictor of mortality even after adjustment for heart failure in peritoneal dialysis patients and should therefore be actively sought and managed in order to improve survival in this population.
Gesehen am 14.01.2019